﻿China’s Move Toward A Low Carbon Economy - Xuedu, Lu; Zhuan, Guiyang; Jiahua, Pan (World Bank, 2012)
Describes improvements in energy efficiency and structural adjustments that are assisting China’s move towards a low carbon economy but emphasizes the need for further technology transfer.